Influence of Leadership Factors and Lean and Modern Management Styles on Quality-of-Care Performance of Hospitals in the USA (Global Journal of Management and Business Research, 2016)
Abstract not found
Keywords: organizational traits; lean management; leadership; management styles; quality-of-care measures